Operando Nanoscale Sensors in Catalysis: All Eyes on Catalyst Particles - Hartman, Thomas (ACS Nano, 2020)
[Image: see text] An era of circularity requires robust and flexible catalysts and reactors. We need profound knowledge of catalytic surface reactions on the local scale (i.e., angstrom–nanometer), whereas the reaction conditions, such as reaction temperature and pressure, are set and controlled on the macroscale (i.e., millimeter–meter). Nanosensors operating on all relevant length scales can supply this information in real time during operando working conditions. In this Perspective, we demonstrate the potential of nanoscale sensors, with special emphasis on local molecular sensing with shell-isolated nanoparticle-enhanced Raman spectroscopy (SHINERS) and local temperature sensing with luminescence thermometry, to acquire new insights of the reaction pathways. We also argue that further developments should be focused on local pressure measurements and on expanding the applications of these local sensors in other areas, such as liquid-phase catalysis, electrocatalysis, and photocatalysis. Ideally, a combination of sensors will be applied to monitor catalyst and reactor “health” and serve as feedback to the reactor conditions.